The Effect of Elderly Exercise on Pain Scale in Patients with Rheumatoid Arthritis - Dedi Supriadi; Reni Purwanti; Jajuk Kusumawaty; Andan Firmansyah; Rosmiati Rosmiati (LPPM STIKes Muhammadiyah Ciamis, 2019)
Rheumatoid arthritis is the most common articular inflammatory disease in the elderly. Rheumatoid arthritis is a chronic, systemic disease that typically develops slowly and is characterized by recurrent inflammation of the diarthrodial joints and associated structures. According to the Ciamis District Office, from the entire Ciamis District Health Center, 17,492 cases of rheumatoid arthritis were diagnosed. To determine the effect of elderly exercise on pain scale in patients with rheumatoid arthritis at the Ciamis Public Health Center. This research method is a pre-experimental design in the form of one group One-Shot Case Study. The population in this study were the elderly aged 45-59 years as many as 129 people. The sampling technique in this research is accidental sampling. The sample in this study were the elderly aged 45-59 years as many as 56 people. The results of the study stated that there was an influence of elderly exercise on the pain scale in patients with rheumatoid arthritis at the Ciamis Health Center, with the significance value of the Wilcoxon test results showing (P = 0.029 <0.05). This means that rheumatoid arthritis can be reduced by doing sports, one of which is by doing elderly gymnastics. Exercise that is done regularly can strengthen the muscles around the joints, reduce pain or aches, improve balance and provide more energy in the body. Conclusion is elderly exercise can affect the pain scale of rheumatoid arthritis sufferers